2016
DOI: 10.1111/andr.12204
|View full text |Cite
|
Sign up to set email alerts
|

Research trends and perspectives of male infertility: a bibliometric analysis of 20 years of scientific literature

Abstract: To carry out an in-depth analysis of the scientific research on male infertility, we performed the first bibliometric analysis focusing on studies involving male infertility worldwide during the period 1995-2014. Analysis of 6357 articles in the field of male infertility showed a significant increasing trend in the number of publications over the period 1995-2014. Obstetrics and Gynecology was an important subject category and Multidisciplinary Sciences was the newest interest. Authors were mainly from Europe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
(48 reference statements)
2
22
0
Order By: Relevance
“…Analyses results shows that scientific productions related to infertility which have been indexed on PubMed over the period 2011-2015 have had a growing trend. The growth in scientific documents in other thematic areas during the past years have been confirmed through studies such as the one by Hou et al in assessing life cycle ( 21 ), cancer ( 14 ), diabetes ( 25 ), reproductive biomedicine ( 26 ) and male infertility ( 27 ). It is not surprising that the USA was the leading country in publication output on infertility, a fact that has also been described in other biomedical fields ( 13 , 26 - 28 ).…”
Section: Discussionmentioning
confidence: 91%
“…Analyses results shows that scientific productions related to infertility which have been indexed on PubMed over the period 2011-2015 have had a growing trend. The growth in scientific documents in other thematic areas during the past years have been confirmed through studies such as the one by Hou et al in assessing life cycle ( 21 ), cancer ( 14 ), diabetes ( 25 ), reproductive biomedicine ( 26 ) and male infertility ( 27 ). It is not surprising that the USA was the leading country in publication output on infertility, a fact that has also been described in other biomedical fields ( 13 , 26 - 28 ).…”
Section: Discussionmentioning
confidence: 91%
“…Zhang et al reported that only one original research article was included in the PubMed database in 1960, while the number increased to 574 articles by 1990, and 866 articles by 2012. Furthermore, 56 male infertility journals were identified in 1995 and it increased to more than 200 in 2012 (Zhang et al, ). These findings could be indirectly linked to higher level of plagiarism due to the exponential increase in the number of available resources.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of (≈ 50%) infertility in human couples, defined as the inability to achieve pregnancy for 12 months or more [8], can be attributed to men [2]. Since the overwhelming body of work on infertility has been mainly concerned with females, the role of males in infertility is rather unexplored, but there has been an upward trend in studying male infertility in the last decade [9].…”
Section: Main Textmentioning
confidence: 99%
“…A large proportion of (≈ 50%) infertility in human couples, defined as the inability to achieve pregnancy for 12 months or more [8], can be attributed to men [2]. Since the overwhelming body of work on infertility has been mainly concerned with females, the role of males in infertility is rather unexplored, but there has been an upward trend in studying male infertility in the last decade [9]. While a number of factors have been invoked to account for male infertility -from diet to tight underwear (reviewed in [5]) -a far less deterministic explanation might be worth our attention: the stochastic redistribution of spermatogonia proteins among sperms.…”
Section: Main Textmentioning
confidence: 99%